HUBUNGAN REGULASI EMOSI DAN DUKUNGAN SOSIAL TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA REMAJA YANG MENGALAMI PUTUS CINTA - Chelsy Ananda Ayu Rahmadhani; Ezelia Beby Wiliano; Nabila Syifa Azikra; Beny Rahim; Jelpa Periantalo; Muhammad Ilham; Dinda Agraiza (CV. Denasya Smart Publisher, 2026)
Separation in a romantic relationship is an experience often encountered by individuals during adolescence and can cause emotional responses such as sadness, disappointment, anger, and feelings of loss. These emotional states are related to adolescents' psychological well-being, especially in the way they express and communicate these feelings to others. Emotional regulation and social support from people around the individual are considered crucial factors in helping young people remain mentally balanced after the end of a romantic relationship. The purpose of this research was to explore how emotional self-regulation, interpersonal assistance, and mental wellness are connected among youth who had gone through romantic separation. Quantitative correlational approach was applied in this research to identify the association among the observed variables. The research involved 65 young individuals aged 15 to 21 years who had experienced the end of a romantic relationship. Respondents were chosen through criterion-based selection, in which only individuals who matched the required characteristics were included. Data were collected using psychological scales measuring emotional regulation, social support, and psychological well-being. After the responses were collected, the data were processed through descriptive computation and correlational analysis. The normality assessment produced a probability score of 0.200, which exceeded 0.05; therefore, the dataset was considered normally spread. Further testing revealed that assistance from the surrounding environment had a strong and statistically meaningful positive association with mental wellness, as indicated by an r value of 0.603 and a probability score of 0.000, which was below 0.05. Emotional self-regulation also moved in the same positive direction with the mental condition of the respondents. In general, the results imply that stronger emotional control and greater external assistance are followed by a more favorable mental state among young people after romantic separation.